Next generation sequencing in women affected by nonsyndromic premature ovarian failure displays new potential causative genes and mutations (2015)
Objective To identify new molecular actors involved in nonsyndromic premature ovarian failure (POF) etiology. Design This is a retrospective case-control cohort study. Setting University research group and IVF medical center. Patient(s) Twelve women affected by nonsyndromic POF. The control group included 176 women whose menopause had occurred after age 50 and had no antecedents regarding gynecological disease. A further 345 women from the same ethnic origin (general population group) were also recruited to assess allele frequency for potentially deleterious sequence variants. Intervention(s) Next generation sequencing (NGS), Sanger sequencing, and bioinformatics analysis. Main Outcome Measure(s) The complete coding regions of 70 candidate genes were massively sequenced, via NGS, in POF patients. Bioinformatics and genetics were used to confirm NGS results and to identify potential sequence variants related to the disease pathogenesis. Result(s) We have identified mutations in two novel genes, ADAMTS19 and BMPR2, that are potentially related to POF origin. LHCGR mutations, which might have contributed to the phenotype, were also detected. Conclusion(s) We thus recommend NGS as a powerful tool for identifying new molecular actors in POF and for future diagnostic/prognostic purposes. © 2015 American Society for Reproductive Medicine.